If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x*x=10*10+24*24
We move all terms to the left:
x*x-(10*10+24*24)=0
We add all the numbers together, and all the variables
x*x-676=0
Wy multiply elements
x^2-676=0
a = 1; b = 0; c = -676;
Δ = b2-4ac
Δ = 02-4·1·(-676)
Δ = 2704
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{2704}=52$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-52}{2*1}=\frac{-52}{2} =-26 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+52}{2*1}=\frac{52}{2} =26 $
| x=10*10+24*24 | | √3h-h/√3=40 | | x-23,6x=60 | | 0.4*(1-x)=1 | | 4(4x-3)=-60 | | 3-2x=6+1x | | 4×x-2=18 | | 5x+13=4x+19 | | 0.3x+2=11+0.03x | | x+(X*2)=1070 | | 5(2x-2)-1x=-3(2-x) | | 3x-4=+7+2x | | 12×x=48 | | 2t=4t-12 | | 0.5(8×+4)=4x+2 | | (x+1)/2-3x(x-1)=(-6(x-1)(x+1)-5)/2 | | 5/4x3/2x+2/x=5 | | Z^4+4z^2+3=0 | | x2+6x+-567=0 | | 2(x-1)(1+x)+(2-x)³+12x=2(2x-1)(1+2x)-x³+8 | | x-8=-28 | | 0=30+10y-16y | | 3(2x-1)+2x-7=3(x+1)-(-3x-1)+3x+2 | | 4000=4160*r*1 | | 4160=4000*r*1 | | 14g=16+6g | | 12r-(-18r)-(-10)=5 | | 108=(12,0+x)x4,5/2 | | 108=(12,0+x)x4,5 | | 5z(z+2)=0 | | 800=x+x0,7 | | 4x-7=19-6x |